Last Word a novel - Adams, Taylor (New York William Morrow, an imprint of HarperCollins Publishers, 2023)
After posting a one-star review for a poorly written--but gruesome--horror novel, Emma Carpenter is dragged into an online argument with the author himself, but when disturbing incidents start happening at night, Emma digs into his life and work, discovering a sadistic man who is capable of anything.
After posting a negative book review, a woman living in a remote location begins to wonder if the author is a little touchy -- or very, very dangerous -- in this pulse-pounding novel of psychological suspense and terror from the critically acclaimed author of No Exit and Hairpin Bridge. Emma Carpenter lives in isolation with her golden retriever Laika, house-sitting an old beach-front home on the rainy Washington coast. Her only human contact is her enigmatic old neighbor, Deek, and (via text) the house's owner, Jules. One day, she reads a poorly written -- but gruesome -- horror novel by the author H.G. Kane, and posts a one-star review that drags her into an online argument with none other than the author himself. Soon after, disturbing incidents start to occur at night. To Emma, this can't just be a coincidence. It was strange enough for this author to bicker with her online about a lousy review; could he be stalking her, too? As Emma digs into Kane's life and work, she learns he has published sixteen other novels, all similarly sadistic tales of stalking and murder. But who is he? How did he find her? And what else is he capable of?
112315
Keywords: Authors -- Fiction; Stalking -- Fiction; Murder; Housesitting; Crime; Book reviews -- Fiction; Psychological fiction; Suspense fiction; Fiction; Novels; Thrillers (Fiction)